Android Apps Security Mitigate Hacking Attacks and Security Breaches - Gunasekera, Sheran; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2020)
Gain the information you need to design secure, useful, high-performing apps that expose end-users to as little risk as possible. This book shows you how to best design and develop Android apps with security in mind: explore concepts that you can use to secure apps and how you can use and incorporate these security features into your apps. You will: Identify data that should be secured Use the Android APIs to ensure confidentiality and integrity of data Build secure apps for the enterprise Implement Public Key Infrastructure and encryption APIs in apps Master owners, access control lists, and permissions to allow user control over app properties Manage authentication, transport layer encryption, and server-side security.
1. Introduction -- 2. Recap of Secure Development Principles -- 3. App Licensing and SafetyNet -- 4. Securing Your Apps at Scale -- 5. Hacking Your App -- 6. The Tool Bag -- 7. Hacking Your App #2. 8. Rooting Your Android Device -- 9. Bypassing SSL Pinning -- 10. Looking Ahead.
Keywords: Mobile computing; Computer programming; Mobile Computing; Programming Techniques